Analysis of transmission and co-movement of rice export prices between Thailand and Vietnam - Duangthip Sirikanchanarak (2018)
© Springer International Publishing Switzerland 2016. Copulas have become one of the most significant new tools to measure nonlinear dependence structure and tail dependence. Combining time-varying copulas and VAR model with kernel density function, this paper proposes a new method, called the time-varying copula-based VAR model, to analyze the transmission and co-movement of rice export prices between Thailand and Vietnam. The time-varying BB1 and BB7 copulas are proposed to measure asymmetric tail dependences. The main findings of this study reveal that there exists obvious co-movement between rice export prices of Thailand and Vietnam, and the time-varying BB7 copula has a better performance than others. In addition, the price transmission between the two markets is bi-directional, and the Vietnamese price is more suitable as price leader in terms of the results of impulse response functions.